The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1186/1746-1596-7-78
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonate-related osteonecrosis of jaw (BRONJ): an anti-angiogenic side-effect?

Abstract: Bisphosphonates are recommended in the treatment of osteoporosis and some cancers, in which case they prevent the appearance of bone metastasis. The patients taking bisphosphonates are at increased risk of developing bisphosphonate-related osteonecrosis of jaw (BRONJ) which is characterised by the presence of an un-healing wound after dental surgery. BRONJ might represent an anti-angiogenic side effect. However, the real number of patients with BRONJ might be higher than currently recorded. Considering the dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 18 publications
1
13
1
Order By: Relevance
“…It was reported that although there was no difference in vascularization between sample groups, there were significantly fewer CD105-positive vessels in BRONJ samples suggesting that neoangiogenesis was suppressed in BRONJ cases [15, 17, 18]. However, angiogenesis is an essential factor in healing of wounds.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that although there was no difference in vascularization between sample groups, there were significantly fewer CD105-positive vessels in BRONJ samples suggesting that neoangiogenesis was suppressed in BRONJ cases [15, 17, 18]. However, angiogenesis is an essential factor in healing of wounds.…”
Section: Discussionmentioning
confidence: 99%
“…As an early therapeutic intervention strategy, biophosphonates treatment could be utilized, however, its efficacy may be controversial. For instance, Jureus et al have reported an effectiveness ratio of 57% for the knee osteonecrosis treatment [21], while other studies showed that bisphosphonates treatments may further exacerbate the osteonecrosis through the potential side effect of anti-angiogenic [22].…”
Section: Discussionmentioning
confidence: 99%
“…15 Aside from the effect on osteoclasts, other BP mechanisms of action have been proposed, including a negative effect on wound healing due to inhibition of angiogenesis. [16][17][18] It has been advocated that caution should be exercised in placing dental implants in patients taking BPs due to possible alterations in the osteogenic wound healing processes, [19][20][21][22][23][24] although the use of systemic BPs has also been advocated as a method to promote osseointegration via reduced bone resorption and remodeling. 25 It is likely that the potency and dose of a particular BP would determine the nature of the influence on osseointegration, with high doses of high-potency BPs, such as ZA, likely to be detrimental.…”
Section: Introductionmentioning
confidence: 99%